Chitosan Coating as a Strategy to Increase Postemergent Herbicidal Efficiency and Alter the Interaction of Nanoatrazine with Bidens pilosa Plants - Sousa, Bruno T.; Carvalho, Lucas B. [UNESP]; Preisler, Ana C.; Saraiva-Santos, Telma; Oliveira, Jhones L. [UNESP]; Verri, Waldiceu A.; Dalazen, Giliardi; Fraceto, Leonardo F. [UNESP]; Oliveira, Halley (American Chemical Society (ACS), 2024)
The atrazine nanodelivery system, composed of poly(ϵ-caprolactone) (PCL+ATZ) nanocapsules (NCs), has demonstrated efficient delivery of the active ingredient to target plants in previous studies, leading to greater herbicide effectiveness than conventional formulations. Established nanosystems can be enhanced or modified to generate new biological activity patterns. Therefore, this study aimed to evaluate the effect of chitosan coating of PCL+ATZ NCs on herbicidal activity and interaction mechanisms with Bidens pilosa plants. Chitosan-coated NCs (PCL/CS+ATZ) were synthesized and characterized for size, zeta potential, polydispersity, and encapsulation efficiency. Herbicidal efficiency was assessed in postemergence greenhouse trials, comparing the effects of PCL/CS+ATZ NCs (coated), PCL+ATZ NCs (uncoated), and conventional atrazine (ATZ) on photosystem II (PSII) activity and weed control. Using a hydroponic system, we evaluated the root absorption and shoot translocation of fluorescently labeled NCs. PCL/CS+ATZ presented a positive zeta potential (25 mV), a size of 200 nm, and an efficiency of atrazine encapsulation higher than 90%. The postemergent herbicidal activity assay showed an efficiency gain of PSII activity inhibition of up to 58% compared to ATZ and PCL+ATZ at 96 h postapplication. The evaluation of weed control 14 days after application ratified the positive effect of chitosan coating on herbicidal activity, as the application of PCL/CS+ATZ at 1000 g of a.i. ha-1 resulted in better control than ATZ at 2000 g of a.i. ha-1 and PCL+ATZ at 1000 g of a.i. ha-1. In the hydroponic experiment, chitosan-coated NCs labeled with a fluorescent probe accumulated in the root cortex, with a small quantity reaching the vascular cylinder and leaves up to 72 h after exposure. This behavior resulted in lower leaf atrazine levels and PSII inhibition than ATZ. In summary, chitosan coating of nanoatrazine improved the herbicidal activity against B. pilosa plants when applied to the leaves but negatively affected the root-to-shoot translocation of the herbicide. This study opens avenues for further investigations to improve and modify established nanosystems, paving the way for developing novel biological activity patterns.
Keywords: Biopolymers; Nanocarriers; Nanoparticle Uptake, Weed Control; Nanopesticides; PSII Inhibition; Surface Charge